2010
DOI: 10.3390/ijerph7072988
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine Disruptors and Obesity: An Examination of Selected Persistent Organic Pollutants in the NHANES 1999–2002 Data

Abstract: Recent evidence suggests that endocrine disrupting chemicals (EDCs) may cause perturbations in endogenous hormonal regulation that predispose to weight gain. Using data from NHANES (1999–2002), we investigated the association between body mass index (BMI), waist circumference (WC) and selected persistent organic pollutants (POPs) via multiple linear regressions. Consistent interaction was found between gender, ln oxychlordane and ln p,p’ DDT. Also, we found an association between WC and ln oxychlordane and ln … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
58
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(60 citation statements)
references
References 30 publications
0
58
1
1
Order By: Relevance
“…Cross-sectional [24,26,27,63] and longitudinal [23,25] studies have reported similar findings. This observation in our population is of great concern and a potential driver for obesity in this population due to the high exposure to pesticides.…”
Section: Discussionmentioning
confidence: 69%
“…Cross-sectional [24,26,27,63] and longitudinal [23,25] studies have reported similar findings. This observation in our population is of great concern and a potential driver for obesity in this population due to the high exposure to pesticides.…”
Section: Discussionmentioning
confidence: 69%
“…As a result of all the interferences caused by POPs, several changes related to appetite, food efficiency, and the ability to exercise could be observed [4].…”
Section: +mentioning
confidence: 99%
“…According to [4], the differences in the values of body mass index caused by POPs in dependence on gender remain unclear. As an example, oxychlordane is associated with BMI increase in males and decrease in females.…”
Section: +mentioning
confidence: 99%
See 1 more Smart Citation
“…Exposure of zebra fish to an environmentally relevant mixture of POPs induces weight gain (10). Several prospective and cross-sectional, mostly North American, studies indicate a positive relationship between serum levels of certain POPs (mainly PCBs and OCPs) and obesity estimates such as BMI and/or waist circumference (11)(12)(13)(14).…”
mentioning
confidence: 99%